2015
DOI: 10.2341/13-357-l
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Dual-Cured Resin Cement Polymerization Induced by High-Intensity LED Curing Units Through Ceramic Material

Abstract: Regardless of the type of curing unit used, indirect irradiation of dual-cured resin cement through a ceramic plate resulted in decreased KHN values compared with direct irradiation. When the irradiation period was extended, only the LED units were able to achieve similar KHN values to those observed under direct irradiation in the presence of plates ≥2.0-mm thick. High-intensity LED units require a shorter irradiation period than halogen and second-generation LED curing units to obtain KHN values similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…This finding corroborates numerous previous studies on degree of conversion and mechanical properties of not only light-cured, resin-based materials [1–7], but also of dual-curing resin cements [17, 19, 20]. The fact that the dual-curing resin cements reacted similarly to purely light-curing, flowable resin composite reflects that most dual-curing resin cements rely to a large extent on effective light-curing [10, 16, 17, 21].…”
Section: Discussionsupporting
confidence: 92%
“…This finding corroborates numerous previous studies on degree of conversion and mechanical properties of not only light-cured, resin-based materials [1–7], but also of dual-curing resin cements [17, 19, 20]. The fact that the dual-curing resin cements reacted similarly to purely light-curing, flowable resin composite reflects that most dual-curing resin cements rely to a large extent on effective light-curing [10, 16, 17, 21].…”
Section: Discussionsupporting
confidence: 92%
“…Studies have reported that the light activation of dual-cured resin cement through the indirect restorations resulted in lower bond strength to dentin, even when used in combination with dual-cured adhesive systems (1,5,7,9). These bond strength reductions are due to the light attenuation caused by indirect restorations, which significantly affect the DC and hardness of the resin cements (1,2,6,8,11,12). Although resin cements are dualcure materials, the self-curing components have not been able to compensate the low light irradiance and produce the same monomer conversion as the light-activated groups (9).…”
Section: Discussionmentioning
confidence: 99%
“…Curing light attenuation compromises the mechanical and adhesive properties of the resin cement because the low light intensity that reaches the resin cement is not sufficient to produce a high degree of conversion (DC) (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Some alternatives included light-emitting diodes (LED) and plasma arcs, with energy emission at 1,600 mW/cm 2 and 2,000 mW/cm 2 , respectively, reducing light activation time (7). Even though there is no clear evidence regarding differences in bonding failure in the three light activation systems, most studies highlight the remarkable reduction in activation time when plasma arcs and LED are used, instead of halogen lamps, for bonding of the brackets to dental surfaces (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%